Advances in prevention and treatment of vancomycin-resistant Enterococcus infection. Issue 6 (December 2016) - Isenman, Heather; Fisher, Dale
Abstract : Purpose of review: This article reviews data, particularly from the last 2 years, addressing the prevention and treatment of vancomycin-resistant Enterococcus (VRE). We focus on infection control, particularly active screening, use of contact precautions as well as pharmacologic options for therapy. This is timely given the evolving priorities in efforts towards the prevention and treatment of multidrug-resistant organisms globally. Recent findings: Key findings include new data regarding the impact of contact precautions on the incidence of VRE colonization and bloodstream infection, new laboratory screening methods, and novel decolonization strategies and treatments. Summary: Additional and specific measures beyond standard precautions for infection prevention of VRE remain controversial. Horizontal measures such as chlorhexidine bathing appear beneficial, as are nontouch environmental cleaning methods. Treatment options for invasive disease have improved considerably in the last decade. Decolonization strategies require further research. Overall, the threat of VRE seems exaggerated.